A 90-day toxicological assessment of KRG hard capsules containing a water extract of Korean red ginseng in Wistar rats - Deok-Chun, Yang; Van Anh, Pham Thi; Young Mi, Cho; Jeong Eun, Kwon; Thuy, Nguyen Thi; Se Chan, Kang; Byoung Man, Kong; Sung Keun, Choi; An, Hoang Van; Thang, Doan Ha; Thao, Bui Thi Huong; Hang, Dinh Thi Thu; et al. (Tạp chí Nghiên cứu Y học, 2025)
The KRG hard capsule was produced by Daedong Korea Ginseng Co. Ltd., with Korean red ginseng (Panax ginseng C. A. Meyer) as its primary component. This study aimed to assess the toxicity of KRG following 90 days of repeated oral dosing. Male and female Wistar rats received the test capsule orally once daily at 120 and 360 mg/kg/day over 90 days. The Korean red ginseng extract administration did not lead to any significant toxicological effects regarding mortality, body weight, hematological parameters, serum biochemistry, gross pathological observations, or histopathological analysis. Consequently, based on this toxicological evaluation, the KRG hard capsules are considered safe and non-toxic. The findings may serve as adequate preclinical evidence to support the initiation of future clinical trials involving KRG.